The Role Of Haji Sulong In Fighting Special Autonomy For Patani Southern Thailand (1947-1954) - Lamato, Husam; Sumarno, Sumarno; Umamah, Nurul (JURNAL HISTORICA, 2017)
This study aims to assess the role of Haji Sulong in Fighting Special Otomomi Pattani southern Thailand in the year 1947- 1954. This study uses historical research while the approach used is sociology politics. The results of show that Changes are most keenly felt by the Patani Malay Community when the government Phibun Songkram the establishment of a political system siamisasi (Rotsaniyom) of political, then Haji Sulong rise spirit Patani Malay society, in the face of political, so that Haji Sulong thus making the people's demands are the demands of 7 cases, to Thai government, the contents of these demands to get a special autonomous region that has its own political and cultural identity. The implications of this research as a hope for other research or information considered to do the kind of research and development at the same time. Keywords: Haji Sulong, special autonomy and Patani